Сборник задач по теоретической электрохимии учебное пособие - Кукоз Ф. И. Федор Иванович; Кудрявцева И. Д. Ирина Дмитриевна; Гончаров В. И. Владимир Иванович; Рыбянец К. А. Константин Александрович (Москва, Высшая школа, 1982)
Авт. указ. на обороте тит. л.